2019
DOI: 10.1111/avsc.12424
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting vegetation change (1974–2015) in hedgerows and forests in an intensively used agricultural landscape

Abstract: Questions: How did hedgerows and forests change in area between 1974 and 2015 and did hedgerows still show the same vegetation composition in 2015? To what degree did the vegetation change in hedgerows and how do these changes compare to changes in forests? What is the nature of the species that changed and, from these, can we make general inferences about possible drivers of change? Location: The countryside in the municipality of Turnhout, province of Antwerp, northern Belgium. Methods: Through a resurvey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…During the past century, herbaceous understorey plant communities homogenised by an increasing presence of nutrient-demanding and shade-tolerant species (Keith et al, 2009;Naaf & Wulf, 2010;Prach & Kopecky, 2018;Staude et al, 2020;Van den Berge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past century, herbaceous understorey plant communities homogenised by an increasing presence of nutrient-demanding and shade-tolerant species (Keith et al, 2009;Naaf & Wulf, 2010;Prach & Kopecky, 2018;Staude et al, 2020;Van den Berge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, if a limited set of taxa replaces many different species across the forest biome, homogenisation can lead to losses of total biodiversity on the scale of the forest biome, even though locally no decline in species richness is registered (Staude et al., 2020). During the past century, herbaceous understorey plant communities homogenised by an increasing presence of nutrient‐demanding and shade‐tolerant species (Keith et al., 2009; Naaf & Wulf, 2010; Prach & Kopecky, 2018; Staude et al., 2020; Van den Berge et al., 2019). Simultaneously, climate change causes an increasing dominance of warm‐adapted species in understorey communities, a process referred to as thermophilisation (Bertrand et al., 2011; De Frenne et al., 2013; Zellweger et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…hedgerows and other linear woody habitats) are traditional components of agricultural landscapes across Europe (Baudry et al ., 2000), and have been repeatedly advocated as a tool for land managers to enhance habitat connectivity (Davies and Pullin, 2007). Indeed, a myriad of studies have shown that hedgerows may function as a refuge habitat or dispersal route for forest herbs among otherwise isolated forest fragments (Corbit et al ., 1999; Sitzia, 2007; Liira and Paal, 2013; Van Den Berge et al ., 2019). From this perspective, hedgerows may be crucial to the long‐term persistence of forest herbs in forest‐devoid agricultural landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…They are subjected to more direct wind momentum load resulting in greater branch production (Zhou et al, 2011), wider anddeeper rooting (Cardinael et al, 2015;Gilman, 1989) and they benefit from agricultural residual inputs such as fertilizers, pesticides and irrigation (Cardinael et al, 2018). Moreover, the hedgerow microclimate is warmer and dryer during the growing season compared to a forest (Vanneste et al, 2020a;Wehling and Diekmann, 2009), and soils are often less acidic (Van Den Berge et al, 2019). And yet, to our knowledge, there is currently no study available on the trends in aboveground stem biomass increments and carbon storage of trees growing in hedgerow systems.…”
Section: Introductionmentioning
confidence: 99%